Eksplorasi Pengalaman Mahasiswa PGSD terhadap Praktik Pendidikan Yoga dalam Meningkatkan Konsentrasi Belajar dan Kesehatan Tubuh - Sukariawan, Made (Adi Widya: Jurnal Pendidikan Dasar, 2026)
This study aims to explore the experiences of Elementary School Teacher Education (PGSD) students regarding yoga practices in improving learning concentration and physical health. This study uses a qualitative approach with a phenomenological method. The research subjects were PGSD students who had participated in yoga practices in lectures. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that yoga practices have a positive impact on improving learning concentration, reducing academic stress, improving physical health, and increasing students' self-awareness. Students experienced increased focus, peace of mind, and a fitter body condition after participating in yoga regularly. This study concludes that yoga education can be an effective holistic learning strategy in supporting students' academic success and well-being.